DOI: 10.34019/ufjf/te/2021/00070
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva e interações planta-polinizador em espécies de bromeliaceae no Parque Estadual do Ibitipoca, Minas Gerais, Brasil

Abstract: Bromeliaceae é caracterizada como um grupo altamente diversificado de plantas monocotiledôneas com distribuição essencialmente neotropical. A Floresta Atlântica, considerada um dos hotspots mundiais de biodiversidade, representa um dos principais centros de diversidade da família, além de elevada riqueza de espécies e endemismo. No domínio Atlântico, muitas espécies de bromélias apresentam distribuição restrita e exibem alta especificidade de habitats, como é o caso das espécies foco do presente estudo. Neoreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
1
2
0
1
Order By: Relevance
“…Th ey were also told of a group in another area, aptly called the Mata dos Monos. Oliveira (2003) also mentioned a group of 10 muriquis in a forest neighboring the park, believed to be the same as was seen by Mendes et al (2003). Ferraz et al (2005), however, indicated that the group consisted of only seven individuals.…”
Section: Ibitipoca State Parksupporting
confidence: 64%
“…Th ey were also told of a group in another area, aptly called the Mata dos Monos. Oliveira (2003) also mentioned a group of 10 muriquis in a forest neighboring the park, believed to be the same as was seen by Mendes et al (2003). Ferraz et al (2005), however, indicated that the group consisted of only seven individuals.…”
Section: Ibitipoca State Parksupporting
confidence: 64%
“…The population of Brachyteles hypoxanthus inhabiting a small forest fragment in Ibitipoca, Lima Duarte, Minas Gerais, Brazil, declined from 10 individuals in 2000 8,9 to just two individuals, one elderly male (BER‐IB; Figure 1A) and one adult male (LUN‐IB), in 2015 10 . To increase the size of this population and preserve its genetics, an intervention was carried out in May and August 2019, involving the translocation of these males to an enclosure, called Muriqui House, constructed 11 kms from their native forest 9 . The Muriqui House project was promoted by “Ibiti Projeto,” a socioenvironmental organization that operates in the area (SISBIO License n° 108 64.438‐6).…”
Section: Introductionmentioning
confidence: 99%
“…10 To increase the size of this population and preserve its genetics, an intervention was carried out in May and August 2019, involving the translocation of these males to an enclosure, called Muriqui House, constructed 11 kms from their native forest. 9 The Muriqui House project was promoted by "Ibiti Projeto," a socioenvironmental organization that operates in the area (SISBIO License n° 108 64.438-6). All procedures carried out in the Muriqui House project were approved by Biodiversity During the present study, the two males were grouped with three females that had been translocated from other populations, localized in the municipalities of Simonésia, Minas Gerais, and Dores do Rio Preto, Espírito Santo, Brazil, 11 and an infant male sired by BER-IB and one of the females.…”
mentioning
confidence: 99%
“…Figura 2 -Diagrama Eh/pH para diferentes espécies de As, em condições ambientais a 25° C. Fonte:Oliveira, 2014 …”
unclassified